2018
DOI: 10.1111/jgh.14076
|View full text |Cite
|
Sign up to set email alerts
|

Persistent reduction of mucosal‐associated invariant T cells in primary biliary cholangitis

Abstract: These findings suggested that MAIT cells were activated, exhausted, and persistently depleted in PBC patients even after ursodeoxycholic acid treatment, possibly as a consequence of persistent liver inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
(94 reference statements)
6
28
0
Order By: Relevance
“…This finding is consistent with previous studies that reported reduced abundance of MAIT cells in peripheral blood 10,25 and in liver tissues 10 of PBC patients compared to healthy controls. Setsu et al observed that depleted MAIT cells were not recovered to normal levels in the blood of PBC patients even after UDCA treatment, suggesting the possibility that MAIT cells were being activated, exhausted, and depleted due to ongoing liver inflammation 10 . Along those lines, the reducedabundance CD8 + CD161 + T cell metacluster in our study also expressed high levels of the immune-exhaustion biomarker PD-1, and one of the constituent clusters expressed high-levels of CTLA4, which is also a marker of exhaustion.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous studies that reported reduced abundance of MAIT cells in peripheral blood 10,25 and in liver tissues 10 of PBC patients compared to healthy controls. Setsu et al observed that depleted MAIT cells were not recovered to normal levels in the blood of PBC patients even after UDCA treatment, suggesting the possibility that MAIT cells were being activated, exhausted, and depleted due to ongoing liver inflammation 10 . Along those lines, the reducedabundance CD8 + CD161 + T cell metacluster in our study also expressed high levels of the immune-exhaustion biomarker PD-1, and one of the constituent clusters expressed high-levels of CTLA4, which is also a marker of exhaustion.…”
Section: Discussionsupporting
confidence: 94%
“…They also summarized the granzyme B expression by MAIT cells correlated with the fibrosis. Setsu et al [76] focused on the PBC patients. MAIT cells were obviously reduced, along with expressing lower levels of activation markers CD69 and IL-7 receptor.…”
Section: Autoimmune Liver Diseasementioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) patients, peripheral blood MAIT cells are numerically and functionally depleted [86]. Similar discoveries were made in terms of several chronic inflammatory conditions that are associated with an increased risk of malignant transformation in the liver, namely hepatitis C virus (HCV) infection [87], primary biliary cholangitis [88], and alcoholic and non-alcoholic fatty liver disease [89]. The degree of MAIT cell deficiency corresponded with disease progression, measured as HCC advancement, extent of liver fibrosis, or serum level of liver damage markers.…”
Section: Hepatic Malignanciesmentioning
confidence: 74%